مذہب کا شاعری و نثرِ اقبال میں اظہار : Religion as it appears in Iqbal’s prose and poetry - Asghar Sial , Dr. Muhammad; Rafiq ul Islam, Dr. Muhammad (Journal of Quranic and Social Studies, 2023)
The center and axis of Allama Iqbal’s thoughts is the religion of Islam. He has used his poetry as a medium for conveying specific purposes. His education started with religious education. The element of religion has been predominant in the expression of their emotions and feelings. He was not influenced by Western thoughts, he tried to spread Islamic thought in the world through his words. Religious influences on his poetry are prominent. The echoes of the Muslim renaissance can be clearly seen in his prose. In his sermons, he made the questions raised in the western minds the subject and wrote on these discussions in private letters. In this sense, his final sermon, "Possibilities of Religion," was the final sermon in which he presented religious concepts in a fresh and contemporary manner. In both prose and poetry, he has discussed his religious experiences and views. His philosophical and theological ideas are crucial for investigation. The Nation of Islam is one, he underscored. Also based on religion is their national identity concept. Allama Iqbal’s beliefs on the Ummah’s oneness are heavily influenced by Sir Syed, Jamaluddin Afghani.